Visual Contradictions Between Cuteness and Sadism: An Analysis of Character Design in Cartoon-Style Adult Animated Film Series - Witharja, Randuwana; Ekawardhani, Yully Ambarsih; Hidayatullah, Taufan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study aims to analyze how character design in the animated Series Happy Tree Friends particularly in the episode “Eyes Cold Lemonade”, constructs a contradictory aesthetic true the contrast between cute visuals and sadistic violence. The study employs Jacques Ranciére’s theoretical framework, focusing on the concept of the distribution of the sensible and dissensus. Data were collected through visual observation of selected scene and analyzed based on character design elements such as body shape, facial expression, and color. The results show that simple shapes, pastel colors, and innocent expression create expectation of a safe and playful visual world, which are then disrupted by extreme violence. This contradiction produces a perceptual tension that intensifies the viewer’s experience. The study concludes that character design functions not only as a visual elements, but also as an aesthetic strategy. These findings highlight the potential of contradictory aesthetic in animation to construct complex visual experience.